Madura on Screen: Analysing the Representation of Madurese Culture and Local Wisdom in YouTube Short Films by Mata Pena Channel - Roifah, Miftahur (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This research aims to analyze the representation of Madurese culture and local wisdom in short films published on YouTube, as well as to identify their impact on viewers, especially the younger generation. The data sources for this study are short films uploaded by the Mata Pena YouTube channel, which has the largest number of followers compared to other YouTube channels that also feature Madurese short films. The Mata Pena YouTube channel has received significant positive recognition from various online media for being perceived as having educational value and good moral messages for its audience. The method used in this research is video content analysis with a qualitative research approach. This study employs Stuart Hall's Cultural Studies theory, which provides a relevant conceptual framework for understanding cultural representation in media. The results clearly indicate that short films focusing on Madurese culture successfully reveal the deep social values and traditions within that community. Through films such as Tata Krama, Loppah Ka Guruh, and Mat Tinggal Abiniah, viewers are invited to understand that the Madurese people highly value politeness, mutual assistance, and respect for teachers. Additionally, the results of the questionnaire show that watching short films about Madurese culture can change the perceptions of the younger generation, reduce negative stigma, and enhance appreciation for the values of politeness.